Arbaeen public health concerns: A pilot cross-sectional survey. Issue 35 (May 2020) - Al-Ansari, Farah; Al Ansari, Mustafa; Hill-Cawthorne, Grant A.; Abdulzahra, Mohammed Saeed; Al-Ansari, Mohammad Basim; Al-Ansari, Basma; Rashid, Harunor; Negin, Joel; Conigrave, Katherine M.
Abstract: Background: Arbaeen is an annual religious procession in Iraq with an estimated 17–20 million participants. Public health risks associated with such a mass gathering can be serious at both local and global levels. This is the first quantitative examination of risk factors for, and symptoms of, infectious disease among Arbaeen participants. Methods: A cross-sectional survey was conducted of a convenience sample of 191 Arbaeen participants in 2017. Interviewers administered a structured questionnaire. Questions included food sources, preventive measures used and symptoms of infectious diseases during the procession. Results: Data were collected for 191 participants (143 males, 58 females). The most prevalent symptoms were respiratory (runny nose: 22.6%, cough: 22.5%). Diarrhoea was reported by 12.6% of participants, with a strong association with high-income country origin and eating (commercial) street food (odds ratios 6.1 and 4.1, respectively, p < 0.05). All symptoms investigated, except breathlessness, were more prevalent in high-income country participants (p < 0.05). Conclusion: Street food and high-income country origin were independent risk factors for respiratory or gastrointestinal infection symptoms in this sample of Arbaeen participants. However, these results cannot be generalised due to possible selection bias. Further studies are required to inform policy development and health system preparedness to reduce Arbaeen-associated health risks.